2016
DOI: 10.1111/jog.13019
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ovarian maldescent: Unusual cause of infertility – A case report and literature review

Abstract: Infertility due to ovarian maldescent is extremely rare and diagnosis can be challenging in the absence of uterine anomalies. We present a case of infertility due to bilateral ovarian maldescent with normal uterine anatomy who conceived after in vitro fertilization and did not require removal of the ovaries. A 19-year-old woman presented with primary infertility. After three failed cycles of ovulation induction/intrauterine insemination and one failed cycle of fresh embryo transfer, the patient underwent lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Maldescended ovaries may be located at various points along the ovarian migration path. In our case, it was seen behind the ascending colon; they have been reported in inguinal hernia[ 5 ] above the pelvic brim[ 6 ] and subhepatic region,[ 7 ] which suggests ovarian maldescent follows the course of the gubernaculum in women. This rare congenital anomaly of the female genital tract may also be accompanied by urinary tract anomalies; therefore, it is advised to review the urological system in the radiological scans and perform ureterolysis during laparoscopic excision, as we did in our case [ Figure 2 ].…”
Section: Discussionmentioning
confidence: 51%
“…Maldescended ovaries may be located at various points along the ovarian migration path. In our case, it was seen behind the ascending colon; they have been reported in inguinal hernia[ 5 ] above the pelvic brim[ 6 ] and subhepatic region,[ 7 ] which suggests ovarian maldescent follows the course of the gubernaculum in women. This rare congenital anomaly of the female genital tract may also be accompanied by urinary tract anomalies; therefore, it is advised to review the urological system in the radiological scans and perform ureterolysis during laparoscopic excision, as we did in our case [ Figure 2 ].…”
Section: Discussionmentioning
confidence: 51%
“…Ovarian maldescent may be unilateral or bilateral, but it has been reported to be more common on the right side and more likely to be located retroperitoneal. 33,34 Our literature research found 39 right UO (52.8%), 23 left UO (31%), and 12 bilateral UO (16.2%). We realised a comparative analysis of the laterality and we discovered that the incidence of the right UO is 59.5% for the symptomatic group (66.6% in children and 57.1% in adults) and 40.7% for the asymptomatic group (with 33.3% left UO).…”
Section: Imaging Diagnosismentioning
confidence: 80%
“…32,33 Another theory is a retarded differential growth of the urogenital ridge's specific region responsible for the formation of the ovaries and fallopian tubes. 34,35 UO may occur in patients with normal uterus. However, although the ovarian embryological development follows a different path than the uterus and fallopian tubes, the UO incidence is higher in the presence of uterine anomalies, particularly the unicornuate uterus (UU) caused by a lack of development of one Müllerian duct or by a disturbed descent to its proper location.…”
Section: Pathogenesis and Associated Malformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, undescended ovary with an incidence of 0.3% can be classified into two main categories: one is associated with congenital uterine anomaly, while the other one is not associated with congenital uterine anomaly (isolated) [ 4 , 5 ]. Undescended ovary and fallopian tubes are more often associated with uterine abnormalities.…”
Section: Introductionmentioning
confidence: 99%